Comparison of Clinical Features and CT Temporal Changes Between Familial Clusters and Non-familial Patients With COVID-19 Pneumonia - Liu, Shuyi; Yuan, Huanchu; Zhang, Bin; Li, Wei; You, Jingjing; Liu, Jing; Zhong, Qingyang; Zhang, Lu; Chen, Luyan; Li, Shaolin; Zou, Yujian; Zhang, Shuixing (Frontiers in Medicine, 2021)
Purpose: This study aimed to compare the clinical characteristics, laboratory findings, and chest computed tomography (CT) findings between familial cluster (FC) and non-familial (NF) patients with coronavirus disease 2019 (COVID-19) pneumonia. Methods: This retrospective study included 178 symptomatic adult patients with laboratory-confirmed COVID-19. The 178 patients were divided into FC (n=108) and NF (n=70) groups. Patients with at least two confirmed COVID-19 cases in their household were classified into the FC group. The clinical and laboratory features between the two groups were compared, as well as the chest CT findings on-admission and end-hospitalization. Results: Compared with the NF group, the FC group had a longer period of exposure (13.1 vs 8.9 days, p <0.001), viral shedding (21.5 vs 15.9 days, p <0.001), and hospital stay (39.2 vs 22.2 days, p <0.001). The FC group showed a higher number of involved lung lobes on admission (3.0 vs 2.3, p=0.017) and at end-hospitalization (3.6 vs 1.7, p <0.001), as well as higher sum severity CT scores at end-hospitalization (4.6 vs 2.7, p=0.005), than did the NF group. Conversely, the FC group had a lower lymphocyte count level (p <0.001) and a significantly lower difference in the number of involved lung lobes (△number) between admission and discharge (p <0.001). Notably, more cases of severe or critical illness were observed in the FC group than in the NF group (p=0.036). Conclusions: Patients in the FC group had a worse clinical course and outcome than those in the NF group; thus, close monitoring during treatment and follow-ups after discharge would be beneficial for patients with familial infections.